Particulars in Greek philosophy : the seventh S.V. Keeling Colloquium in Ancient Philosophy - Sharples, R. W. (Philosophia Antiqua, 2010)
Ancient Greek philosophy has been criticised, for example by the late Bernard Williams, for emphasising the universal at the expense of the particular. Six leading scholars consider what the Greeks themselves, from Plato to the period of the Roman Empire, had to say on this issue in the contexts of ethics, psychology, metaphysics and cosmology. Ancient views are compared with modern ones, and the influence of the former on the latter is considered.